Differentially expressed microRNAs in aneuploid preimplantation blastocysts: a systematic review - Almutlaq, Arwa; Viñals Gonzalez, Xavier; SenGupta, Sioban (Frontiers in Reproductive Health, 2024)
MicroRNAs are small noncoding genes with gene expression regulatory function. Their emergence as potential diagnostic biomarker for many diseases has gained a specific interest among researchers. Observations of changes in miRNA levels correlating with aneuploidy in early embryos raise the prospective of employing miRNA as biomarkers to assess the embryo quality. To identify and gather the miRNAs with potential link to chromosomal abnormalities in embryos from previous research, we conducted a systematic search using four databases, including Embase, Medline, Web of Science, and Cochrane databases in accordance with PRISMA guidelines. Out of 200 identified records, only seven met the inclusion criteria. Five miRNAs: miR-19b, miR-517c, miR-518e, miR-522, miR-92a, and miR-106a exhibited persistent downregulation in aneuploid blastocysts in at least two studies. These miRNAs are members of important miRNA clusters, associated with abnormal expression in studies on reproductive failure. Pathway analysis revealed their involvement in regulating gene transcription, as well as cell cycle progression and apoptosis. The changes detected in the miRNA expression in aneuploid embryos across different studies support the aneuploidy and miRNA relationship and prospect miRNA as a valuable tool for the assessment of embryo quality. Collectively, these observations highlight the role of miRNAs in embryonic development, and their involvement in genetic abnormalities that occur in embryos, such as aneuploidy, indicating their potential implementation to improve the embryo selection and reproductive outcomes.